Unlocking Productivity and Well-Being: Exploring the Four-Day Workweek and Design Thinking for Its Implementation - Muhammad Naufal Sugiarto; Fakhira Salsabilla; Asep Taryana; Dinda Naura Fathya (Syntax Corporation Indonesia, 2024)
Work life balance is the most important factor for employees of this generation in keeping their jobs. Meanwhile, the five-day workweek working system that is implemented today is raising concerns as the workload increases which leads to work life imbalance, declining productivity, also burnouts and mental-health issues of the employees. To overcome it, this study proposes a four-day workweek system as a possible solution. The study aims to explore the potential benefits of a fourday workweek as well as the usage of design thinking method in enabling a successful implementation of the system. By examining factors like work scheduling, business needs, and employee satisfaction, this study also seeks to optimize the four-day workweek model. The study finds that four-day work week can increase employees’ well-being, mainly in improving work-life balance and decreasing fatigue and stress with more day off, also increases job satisfaction and employee’s motivation to contribute more to their jobs. Using design thinking method may help the implementation of this system with understanding employee needs and preferences, identifying potential challenges and develop solutions, optimizing collaboration and communication, and evaluating and iterating the whole process. By prioritizing human-centered solutions and iterating based on feedback, organizations can create a work model that benefits both employees and the organization's overall goals.